2011
DOI: 10.1088/1475-7516/2011/12/020
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on ultracompact minihalos from extragalactic γ-ray background

Abstract: It has been proposed that ultracompact minihalos (UCMHs) might be formed in earlier epoch. If dark matter is in the form of Weakly Interacting Massive Particles (WIMPs), UCMHs can be treated as the γ-ray sources because of the dark matter annihilation within them. In this paper, we investigate the contributions of UCMHs formed during three phase transitions (electroweak symmetry breaking, QCD confinement and e + e − annihilation) to the extragalactic γ-ray background. Moreover, we use the Fermi-LAT observation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 42 publications
2
61
1
Order By: Relevance
“…In Refs. [7,8,19], the authors have investigated the γ-ray flux from the nearby and extra-Galactic UCMHs. Besides these high energy photons, the neutrinos would be produced together with the γ-ray in the process of dark matter annihilation.…”
Section: B Neutrino Signals From Nearby Ucmhsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Refs. [7,8,19], the authors have investigated the γ-ray flux from the nearby and extra-Galactic UCMHs. Besides these high energy photons, the neutrinos would be produced together with the γ-ray in the process of dark matter annihilation.…”
Section: B Neutrino Signals From Nearby Ucmhsmentioning
confidence: 99%
“…So it is expected that these new interesting structures would have an effect on the cosmological evolution, such as reionization and recombination, due to the dark matter annihilation within them if the dark matter is composed of weakly interacting massive particles (WIMP) [4][5][6], such as neutralinos. According to the theory, dark matter can annihilate into the standard particles, such as photons(γ), electrons and positrons(e + , e − ), and UCMHs would become one kind of possible high energy astrophysical sources, such as γ-ray sources [7][8][9]. The other kind of important product of dark matter annihilation is the neutrino.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5], the authors studied the impact of UCMHs on the cosmological ionization and obtained the constraints on the abundance of them. If high energy photons are produced by the dark matter annihilation, the UCMHs will become one kind of astrophysical sources and they can contribute to the γ-ray background [6][7][8][9][10][11][12]. The authors of Refs.…”
mentioning
confidence: 99%
“…In Ref. [9], the authors investigated the contributions of UCMHs to the extragalactic gamma-ray background and found that the constraints increase with the dark matter mass: f UCMHs ∼ 10 −5 and ∼ 10 −3 for the dark matter mass M χ ∼ 10GeV and ∼ 1TeV, respectively. These constraints are stronger than the results obtained from the CMB data by about one orp-1 der of magnitude (see the Fig.…”
mentioning
confidence: 99%